Дослідження фаз клітинного циклу та плоїдності ядерної ДНК клітин печінки статевонезрілих щурів при хронічному токсичному гепатиті та корекції лізиноприлом = Research of cell cycle phases and nuclear DNA ploidy in immature liver cells of rats with chronic toxic hepatitis and lisinopril correction - Rikalo, N. A.; Beregovenko, Y. M. (Journal of Education, Health and Sport, 2016)
Rikalo N. A., Beregovenko Y. M. Дослідження фаз клітинного циклу та плоїдності ядерної ДНК клітин печінки статевонезрілих щурів при хронічному токсичному гепатиті та корекції лізиноприлом = Research of cell cycle phases and nuclear DNA ploidy in immature liver cells of rats with chronic toxic hepatitis and lisinopril correction. Journal of Education, Health and Sport. 2016;6(1):219-228. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45343 http://ojs.ukw.edu.pl/index.php/johs/article/view/3354 https://pbn.nauka.gov.pl/works/710097 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 25.01.2016. дослідження фаз клітинного циклу та плоїдності ядерної днк клітин печінки статевонезрілих щурів при Хронічному токсичному гепатиті та корекції лізиноприлом RESEARCH OF CELL CYCLE PHASES AND NUCLEAR DNA PLOIDY IN IMMATURE LIVER CELLS OF RATS WITH CHRONIC TOXIC HEPATITIS AND LISINOPRIL CORRECTION Н. А. Рикало, Ю. М. Береговенко N. A. Rikalo, Y. M. Beregovenko Вінницький національний медичний університет імені М.І. Пирогова Vinnitsa National Pirogov memorial Medical University Summary The results of experimental studies on the impact angiotensin inhibitor converting enzyme - lisinopril on the processes of reparative regeneration of liver tissue of rats with chronic toxic hepatitis were present. The aim: to investigate the effect of lisinopril on phases of the cell cycle ploidy and nuclear DNA of liver cells of rats model of chronic toxic hepatitis (CTH) in rats. Experimental studies conducted on 34 white laboratory immature rats with an initial body weight 50-70 gr. CTH was modelling by intragastric administration of 0,1 ml/100 g weight CCl4 oil solution twice a week in combination with a 5% solution of ethanol for six weeks. Lisinopril (at a dose of 20 mg/kg) was introduced into the stomach simultaneously with hepatotoxins daily for six weeks. Conclusion. Administration of lisinopril with hepatotoxins promotes the process of reparative regeneration of liver tissue due to the hyperplasia of hepatocytes, as indicated by the increase of the percentage of hepatocytes with diploid set of DNA reduction of polypoid nuclei amount and restoration of the proportion of nuclei in the range of G0-G1. Key words: chronic toxic hepatitis, rats, reparative regeneration, mechanism, cell cycle, DNA ploidy nuclear. Резюме У статті наведені результати експериментальних досліджень по вивченню впливу інгібітора ангіотезин-перетворюючого ферменту лізиноприлу на процеси репаративної регенерації тканини печінки щурів із хронічним токсичним гепатитом. Мета роботи: дослідити вплив лізиноприлу на фази клітинного циклу та плоїдність ядерної ДНК клітин печінки щурів на моделі хронічного токсичного гепатиту (ХТГ) у щурів. Експериментальні дослідження проведені на 34 білих лабораторних статевонезрілих, з початковою масою тіла 50-70г. ХТГ, змодельованим інтрагастральним введенням олійного розчину ССl4 в дозі 0,1 мл/100 г маси двічі на тиждень у комбінації з 5% розчином етанолу в якості пиття впродовж шести тижнів. Паралельно із гепатотоксинами щодня протягом шести тижнів інграгастрально вводили лізиноприл (в дозі 20мг/кг). Висновок. Лікувально-профілактичне введення лізиноприлу одночасно із гепатотоксинами сприяє процесам репаративної регенерації тканини печінки за механізмом гіперплазії, на що вказує збільшення відсотку гепатоцитів із диплоїдним набором ДНК, зменшення відсотку поліплоїдних ядер та відновлення частки ядер у інтервалі G0-G1. Ключові слова: хронічний токсичний гепатит, щурі, репаративна регенерація, мезанізми, клітинний цикл, плоїдність ядерної ДНК.